2008
DOI: 10.2143/ac.63.2.2029519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucometabolic disorders on the formation of coronary collaterals in occlusive coronary artery disease

Abstract: In conclusion, our study results, which are in agreement with previous results, indicate that not only diabetic glucose tolerance but also impaired glucose tolerance has an adverse impact on the development of coronary collaterals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Additionally, the Interventional Management of Stroke III Trial recently showed that a robust collateral grade was associated with better recanalization, reperfusion and clinical outcome 26. Since coronary collateral development has been shown to be worse in diabetic patients than in non-diabetic patients with myocardial ischemia,27 we suggest that the low rate of recanalization for diabetes with LVO may be associated with poor collateral flow in diabetes. However, this assumption needs to be validated in future studies.…”
Section: Discussionmentioning
confidence: 78%
“…Additionally, the Interventional Management of Stroke III Trial recently showed that a robust collateral grade was associated with better recanalization, reperfusion and clinical outcome 26. Since coronary collateral development has been shown to be worse in diabetic patients than in non-diabetic patients with myocardial ischemia,27 we suggest that the low rate of recanalization for diabetes with LVO may be associated with poor collateral flow in diabetes. However, this assumption needs to be validated in future studies.…”
Section: Discussionmentioning
confidence: 78%
“…Prior studies that examined the role of clinical factors on coronary collateralization have yielded conflicting results: For example, in some studies, diabetes mellitus was found to be a negative predictor of the presence of collaterals [30], [31], [32], [33], [34], while in others it was not [35], [36], [37], [38], [39]. In the present study, we found a negative association between diabetes mellitus and coronary collateralization and a positive association with hyperlipidemia, but independent of HMG-CoA reductase inhibitor therapy as has been reported by others [40], [41].…”
Section: Discussionmentioning
confidence: 99%
“…There is objective evidence of left ventricular systolic/ diastolic dysfunction in patients with CSFP [36,37]. However, the effect of CSFP on left atrial function has been minimally investigated.…”
Section: Csfp and Left Atrial Functionmentioning
confidence: 99%